2018
DOI: 10.4103/sjg.sjg_562_17
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of interleukin-17 and interleukin-22 in the serum and the lower esophageal sphincter of patients with achalasia

Abstract: Background/Aim:We studied the expression of interleukin-17 and interleukin-22 in the serum and the lower esophageal sphincter (LES) in healthy individuals and in patients diagnosed with achalasia (AC) to gain a better understanding of the etiopathogenesis of AC.Patients and Methods:Our study comprised 14 randomly selected patients with AC who underwent peroral endoscopic myotomy and 14 randomly selected healthy individuals who served as controls. Venous blood samples were evaluated in all study subjects to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
(35 reference statements)
0
6
1
1
Order By: Relevance
“…As mentioned above, information on the serum cytokine profiles in achalasia is limited and therefore, the results of previous studies may not be entirely comparable with those from the present study. The apparent differences reported between the present and previous studies ( 9 , 10 ) may also be explained by the heterogeneity in the characteristics of the patients, the controls and the methodology used. In effect, although all authors applied immunoenzymatic assays for marker detection, the kits utilized were different.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…As mentioned above, information on the serum cytokine profiles in achalasia is limited and therefore, the results of previous studies may not be entirely comparable with those from the present study. The apparent differences reported between the present and previous studies ( 9 , 10 ) may also be explained by the heterogeneity in the characteristics of the patients, the controls and the methodology used. In effect, although all authors applied immunoenzymatic assays for marker detection, the kits utilized were different.…”
Section: Discussioncontrasting
confidence: 88%
“…Few studies have measured the levels of circulating inflammatory biomarkers, namely cytokines, chemokines and growth factors, and deduced their differences between patients with achalasia and controls. Wang et al ( 9 ) previously measured the expression of IL-17 and IL-22 in the serum, which was collected before and during peroral endoscopic myotomy. It was found that the levels of IL-17 and IL-22 were significantly increased in the 14 patients who were diagnosed with achalasia compared with those in 14 healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Serological analysis studies also found that pro-inflammatory cytokines (IFN-γ, IL-17, and IL-22), anti-inflammatory cytokines (IL-4 and TGF-β), and chemokines (monokine induced by IFN-γ and IFN-γ induced protein-10) were significantly upregulated in patients with achalasia, the most prominent of which were proinflammatory related factors. [84][85][86]…”
Section: Inflammation and Immunitymentioning
confidence: 99%

Achalasia alters physiological networks depending on sex

Furuzawa-Carballeda,
Barajas-Martínez,
Olguín-Rodríguez
et al. 2024
Sci Rep